Pertanggungjawaban Hukum Pengelola Parkir Terhadap Kehilangan Kendaraan Di Makassar Berdasarkan Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Wahdaniah Baharuddin (LUTUR Law Journal, 2024)
The management of motorized vehicle parking in Makassar City is one of them carried out by parking services owned by the Makassar City government, namely the Makassar Raya Parking Company of Makassar City. The main problem in the management of parking services is the safety and comfort of vehicles parked at the parking service management site, this is felt by consumers due to a lack of responsibility by the parking service, such as it is not clear who is responsible if a vehicle is lost while still in the parking lot. This study aims to determine the implementation of the legal responsibility of parking managers for the loss of two-wheeled motorized vehicles based on Law Number 8 of 1999 concerning Consumer Protection in Makassar City. This research is a descriptive perspective. This type of research is normative legal research. The approach is carried out by examining the literature or literature study and directly observing conditions in the field related to the problem under study and conducting interviews with the Makassar Raya Parking Area company. The sources of legal materials used are primary and secondary legal materials which are then interpreted and analyzed qualitatively. The implementation of the legal responsibility of parking managers for the loss of two-wheeled motorized vehicles in Makassar City under the auspices of the Makassar Raya Parking Company is not in accordance with Law Number 8 of 1999 concerning Consumer Protection. Based on Article 18 paragraph (1) of Law Number 8 of 1999 concerning Consumer Protection, the inclusion of standard clauses by business actors in parking services stating the transfer of responsibility of business actors is prohibited, and based on Article 18 paragraph (3) of the Consumer Protection Law, the clause is declared null and void.